History of Exposure to Pesticides With Symptoms of Poisoning in Children in Agricultural Areas; Case-Control Study In West Seram Regency - Ilyas Ibrahim; Sahrir Sillehu (Medsci Publications, 2023)
The high use of pesticides can cause environmental pollution, poisoning and accumulate in agricultural products, resulting in a negative impact on public health. Pesticides attack the nervous system, liver, immune system and balance hormonal disturbances that interfere with the growth and development of children. Children are a group at risk of exposure to pesticides because they participate in agricultural activities and live near agricultural areas. The purpose of this study was to analyse the history of exposure to pesticides with symptoms of poisoning in elementary school children in agricultural areas. This type of research is analytic observational with a case-control study design. The study involved 90 elementary school children who were taken using inclusion criteria based on their area of residence. There are 90 children living in agricultural areas. Collecting data using a questionnaire, observation and health examination. Data analysis used the Chi-square test to see the proportion and relationship of variables. The results showed that there was a relationship between children's involvement in cleaning vegetables (p=0.01; OR=3.89), tying vegetables (p=0.037; OR=4.74), and children's personal hygiene after playing (p=0.04; OR=3.06) which significantly increased risk of exposure to pesticides with symptoms of poisoning. Conclusion; There is a relationship between history of exposure to pesticides and symptoms of poisoning in children.